Oxaliplatin plus Capecitabine in the Perioperative Treatment of Locally Advanced Gastric Adenocarcinoma in Combination with D2 Gastrectomy: NEO‐CLASSIC Study. (25th June 2019) - Yu, Yiyi; Fang, Yong; Shen, Zhenbin; Wang, Yan; Yan, Min; Cao, Hui; Liu, Yingbin; Wang, Xuefei; Cui, Yuehong; Liu, Fenglin; Chen, Weidong; Li, Wei; et al.
Abstract: Lessons Learned: The NEO‐CLASSIC study provided valuable insight for the clinical efficacy and tolerability profiles of perioperative chemotherapy with oxaliplatin and capecitabine, plus gastrectomy, in patients with localized resectable gastric cancer. The study was designed to explore the potential survival benefits of an eight‐cycle, perioperative oxaliplatin and capecitabine (XELOX) schedule in the above‐mentioned setting and to explore the feasibility of prolonging the cycles of preoperative chemotherapy. The projected endpoint was not met. Background: This multicenter, open‐label study (NEO‐CLASSIC) evaluated the efficacy and safety of oxaliplatin and capecitabine (XELOX), plus D2 gastrectomy, in localized resectable gastric cancer. Methods: Patients aged 18–75 years with histologically‐confirmed gastric adenocarcinoma (stage T2–4a/N+M0) were given eight cycles of XELOX (four preoperatively, four postoperatively). Each 3‐week cycle comprised capecitabine 1, 000 mg/m 2 twice daily on days 1–14 and oxaliplatin 130 mg/m 2 on day 1. Curative D2 gastrectomy was scheduled 2–4 weeks after the last preoperative cycle. The primary objective of the study was to determine the objective response rate (ORR) of XELOX in the preoperative setting. Sample size was calculated by assuming that a minimum of 47 cases would be required to increase the ORR by 15% (from 40% to 55%). With an estimated 10% dropout rate, 55 patients would have to be recruited. Results: Fifty‐five patients were enrolled, and one was excluded because of screening failure. R0 resections were achieved in 45 of 54 intent‐to‐treat patients (83.3%), and four patients received R1 resections (Fig. 1). There were no complete responses, 27 (50.0%) partial responses, 22 cases (40.7%) of stable disease, and 4 (7.4%) of progressive disease. The objective response rate was 50.0%. Median follow‐up was 52.97 months; 30 patients (55.6%) had disease progression (Table 1), and median progression‐free survival was 20.10 (95% confidence interval: 4.31—35.89) months; median overall survival was 30.77 months (95% confidence interval was not yet available) (Fig. 2). Fifty‐four patients completed 209 cycles of preoperative chemotherapy; 42 patients received 133 cycles of postoperative chemotherapy (Table 3). The rate of grade 3–4 adverse events was 8.5% (29/342 cycles); the most frequent events were neutropenia (9/342 cycles) and leukopenia (4/342 cycles). Conclusion: These findings suggest that combination therapy with capecitabine and oxaliplatin as perioperative chemotherapy, followed by D2 gastrectomy, is effective and safe in late‐stage, locally advanced gastric cancer. Although enrollment exceeded the 47 patients required to identify an increase in the ORR by 15% (from 40% to 55%), results did not meet the primary endpoint.